Preparation method and ultraviolet shielding application of titanium hydride / lignin two-dimensional nanosheet composite material

By combining titanium hydride with lignin two-dimensional nanosheets, and using pickling and sonication technology, the biocompatibility and cytotoxicity of inorganic anti-ultraviolet nanoparticles are solved, achieving efficient ultraviolet shielding and anti-oxidation effects.

CN119799024AActive Publication Date: 2025-04-11CHANGZHOU UNIV

Patent Information

Application Number
CN202510100587.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-22
Publication Date
2025-04-11
Estimated Expiration
2045-01-22

AI Technical Summary

Technical Problem

In the prior art, inorganic anti-ultraviolet nanoparticles are cytotoxic and lack biocompatibility, and inorganic components combined with natural organic components for anti-ultraviolet materials have not been reported.

Method used

The preparation method of titanium hydride (TiH2) and lignin two-dimensional nanosheet composite material was adopted. The oxide layer of titanium hydride was removed by pickling and sonication to form TiH1.92, and the lignin nanosheets and titanium hydride were evenly dispersed by ball milling and ultrasonic treatment.

Benefits of technology

The oxidation resistance and ultraviolet shielding ability of composite materials are improved, the ultraviolet shielding ability of nanocomposite materials is significantly improved, the agglomeration phenomenon is avoided, and the material itself is fully harnessed for its ultraviolet and oxidation resistance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005254084120000041
    Figure BDA0005254084120000041
  • Figure HDA0005254084130000011
    Figure HDA0005254084130000011
  • Figure HDA0005254084130000012
    Figure HDA0005254084130000012
Patent Text Reader

Abstract

The invention relates to the technical field of ultraviolet shielding materials, in particular to a preparation method of a TiH2 / lignin two-dimensional nanosheet composite material and ultraviolet shielding application of the TiH2 / lignin two-dimensional nanosheet composite material. Firstly, lignin deionized water dispersion liquid is subjected to ball milling and then subjected to vacuum freeze drying, flake lignin is obtained, then TiH2 powder is subjected to ball milling and drying and then dissolved in a nitric acid aqueous solution for acid pickling, washing and drying to obtain TiH2 powder, the TiH2 powder and the flake lignin are dispersed in the aqueous solution to be mixed and subjected to ultrasonic treatment, and the composite material is obtained. And separating a solid from the obtained suspension, and freeze-drying to obtain the TiH2 / lignin nanosheet composite material. The lignin nanosheets and the TiH2 are compounded through ultrasonic treatment, the agglomeration phenomenon between the lignin nanosheets is avoided, meanwhile, the TiH2 forms a uniform nanosheet structure, the reaction of the TiH2 and external free radicals is more facilitated to form TiO2, and good ultraviolet shielding capacity and oxidation resistance are shown on the whole.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of ultraviolet shielding materials, and in particular to a preparation method and application of a TiH2 / lignin two-dimensional nanosheet composite material. Background Art

[0002] As the ozone layer is destroyed, more ultraviolet rays from the sun reach the earth's surface. The high energy of ultraviolet rays can cause sunburn, premature skin aging, and even skin cancer. Inorganic nanoparticles as UV protection have high mass density and photocatalytic activity limitations, inherent cytotoxicity and lack of biocompatibility restrict their application. Therefore, combining inorganic ingredients with natural organic ingredients in sunscreens has become an emerging research direction in the field of UV protection.

[0003] Titanium hydride (TiH2) is a gray-black inorganic compound. During the application process, because the active hydrogen in titanium hydride shows great potential to eliminate hydroxyl radicals, titanium dioxide (TiO2) can be formed in situ. This titanium dioxide has an anti-ultraviolet effect and has a strong ability to absorb ultraviolet light during the OH radical scavenging process. At the same time, titanium hydride may reflect and scatter ultraviolet rays by forming a physical barrier, reducing the direct contact and damage of ultraviolet rays to the skin. However, titanium hydride powder is directly used for ultraviolet shielding applications, and there is a problem of poor biocompatibility. Compared with the original titanium hydride powder, titanium hydride nanosheets have a higher specific surface area and can better absorb free radicals to provide antioxidant properties and shield ultraviolet rays.

[0004] Chinese patent CN108456314A mixes 2,4-dihydroxybenzophenone and dihaloalkane, reacts in an ice-water bath under an acid-binding agent and solvent environment to obtain a reactive UV absorber, dissolves the reactive UV absorber in an organic solvent, and drops it into the alkali solution of lignin to obtain a lignin polymer UV protective agent. A large amount of toxic organic solvents are used in the preparation process. Chinese patent CN111228141A dissolves lignin and dopamine hydrochloride in tris (hydroxymethyl) aminomethane-hydrochloric acid buffer, adds ammonium persulfate and hydrogen peroxide, stirs for 8 to 36 hours, centrifuges and dialyzes the upper layer of liquid to obtain a lignin-polydopamine composite material. The preparation process takes a long time and the operation is complicated. So far, there has been no report on combining the inorganic component TiH2 with the natural organic component lignin for anti-ultraviolet materials. Summary of the invention

[0005] In order to solve the harm of organic UV shielding materials to human body and environment and the problem that inorganic anti-UV nanoparticles as UV protection are limited by high mass density and photocatalytic activity, inherent cytotoxicity and lack of biocompatibility, the present invention proposes a method for preparing a TiH2 / lignin two-dimensional nanosheet composite material.

[0006] In order to achieve the purpose of the present invention, the following technical solutions are adopted:

[0007] A method for preparing a titanium hydride / lignin two-dimensional nanosheet composite material comprises the following steps:

[0008] (1) An appropriate amount of lignin and deionized water are mixed uniformly by stirring (mass ratio is 1:10-30), and the mixture is ball-milled in a ball mill at 200-300 rpm for 1-3 h to obtain a lignin nanosheet mixture. The precipitate obtained after centrifugation is freeze-dried to obtain lignin nanosheets.

[0009] (2) Mix an appropriate amount of titanium hydride and deionized water by stirring (mass ratio is 1:10-20), and ball mill the mixture in a ball mill at 300-600 rpm for 1-3 hours to obtain a titanium hydride mixture, which is then dried after centrifugation. Mix HNO3 and water to prepare an acid wash solution to obtain a nitric acid aqueous solution with a mass fraction of 0.5% to 5%. Immerse an appropriate amount of titanium hydride powder in the prepared acid wash solution for acid wash (0.05 g / mL to 0.25 g / mL), and the acid wash time is 90 to 180 seconds. After acid wash, the titanium hydride powder is thoroughly washed with deionized water and centrifuged to remove the residual acid on the surface, and then dried in an oven.

[0010] (3) The powder obtained in step (1) (2) is added to deionized water in a ratio of 1: (0.2-6) and mixed evenly (0.1 g / mL-0.45 g / mL). The obtained suspension is added to an ultrasonic kettle and ultrasonically treated for 10-30 minutes at a power of 200-300 W. The mixture is centrifuged at a speed of 5000-10000 rpm for 3-10 minutes, washed with deionized water, and freeze-dried after centrifugation to obtain a titanium hydride / lignin two-dimensional nanosheet composite material.

[0011] Compared with the prior art, the present invention has the following beneficial effects:

[0012] The present invention obtains TiH by acid washing TiH2 1.92 , removing part of the oxide layer and dirt, making TiH 1.92It has better antioxidant and UV shielding properties. Lignin is subjected to ball milling ultrasonic treatment to obtain a lignin flaky structure with a smaller particle size. Lignin nanosheets and titanium hydride are subjected to ultrasonic treatment, and the groups on the surface of titanium hydride and the rich functional groups on the surface of lignin form hydrogen bonds to avoid the agglomeration phenomenon between lignin nanosheets, so that the dispersed nano-sized lignin sheets have excellent UV absorption capacity. At the same time, after ultrasonic treatment, titanium hydride is more dispersed so that part of lignin is intercalated in the titanium hydride structure, and titanium hydride forms a uniform nano-flaky structure, which is more conducive to titanium hydride reacting with external free radicals to form TiO2, providing better UV shielding ability. Part of the Ti in titanium hydride changes with time to oxidize and absorb free radicals to become TiO2, which continuously improves the UV resistance of the composite material and has excellent antioxidant properties. The synergistic effect of lignin and titanium hydride significantly improves the UV shielding ability of the nanocomposite material. The titanium hydride / lignin nanosheet composite material prepared by the above method of the present invention has a higher specific surface area, avoids agglomeration phenomenon, and gives full play to the UV resistance and antioxidant properties of the material itself. BRIEF DESCRIPTION OF THE DRAWINGS

[0013] Figure 1 The lignin and TiH prepared in Example 1 1.92 、TiH 1.92 / lignin samples and TiH prepared in Example 3 1.92 / XRD spectra of lignin samples after ultrasonic treatment for 10min and 30min;

[0014] Figure 2 The lignin nanosheets and TiH prepared in Example 1 1.92 、TiH 1.92 / lignin flake structure, TiH prepared in Example 3 1.92 Solid UV absorption spectra of TiH2 flake structure and TiH2 / lignin flake structure samples prepared in Comparative Example 1;

[0015] Figure 3 The lignin nanosheets and TiH prepared in Example 1 1.92 、TiH 1.92 / lignin flake structure, TiH prepared in Example 3 1.92 Solid UV transmission spectra of TiH2 flake structure and TiH2 / lignin flake structure samples prepared in Comparative Example 1;

[0016] Figure 4 The TiH prepared in Example 1 1.92 、TiH 1.92 / TEM spectrum of lignin flake structure in the scale range of 200nm and 100nm;

[0017] Figure 5The lignin nanosheets and TiH prepared in Example 1 1.92 / DPPH scavenging rate of lignin flake structure.

[0018] Figure 6 The SPF values ​​of various examples, comparative examples, lignin and titanium hydride are shown in FIG. DETAILED DESCRIPTION

[0019] Example 1: (1) An appropriate amount of lignin and deionized water were mixed by stirring (mass ratio of 1:20) to obtain a mixed solution, and the mixed solution was ball-milled in a ball mill at 200 rpm for 2 h to obtain a lignin nanosheet mixed solution. The precipitate obtained after centrifugation was freeze-dried to obtain a lignin nanosheet structure.

[0020] (2) Mix an appropriate amount of TiH2 and deionized water by stirring (mass ratio is 1:10) to obtain a mixed solution, and ball mill the mixed solution in a ball mill at 400 rpm for 3 hours to obtain a TiH2 mixed solution. Centrifuge and dry. Mix HNO3 and water to prepare an acid wash solution to obtain a 3% nitric acid aqueous solution. Immerse an appropriate amount of titanium hydride powder in the prepared acid wash solution for acid washing (0.15 g / mL) for 100 seconds. The TiH2 after acid washing 1.92 The powder was washed thoroughly with deionized water, centrifuged to remove residual acid on the surface, and dried in an oven.

[0021] (3) The powder obtained in step (1) (2) was added to deionized water in a mass ratio of 2:1 and mixed evenly (0.15 g / mL). The obtained suspension was added to an ultrasonic kettle and ultrasonically treated for 20 minutes at a power of 250 W. The suspension was centrifuged at a speed of 10,000 rpm for 6 minutes, washed with deionized water, and freeze-dried after centrifugation to obtain TiH 1.92 / lignin two-dimensional nanosheet composites.

[0022] The TiH prepared in this example 1.92 The X-ray powder diffraction experiment of the composite material was carried out, its morphology and structure were observed under a transmission electron microscope, and its ultraviolet shielding effect was tested under a solid ultraviolet instrument.

[0023] XRD spectrum Figure 1 Shown: TiH 1.92 The material shows multiple diffraction peaks, which are the diffraction peaks of TiH2; TiH 1.92 、TiH 1.92 / TEM spectrum of lignin flake structure Figure 4 As shown. a) and b) are the preparation of TiH in Example 1 1.92 Structure; c) and d) are TiH 1.92TEM spectrum of the lignin flake structure at 200nm and 100nm scale after 30min of ultrasound. 1.92 and lignin are stacked in sheets to provide a larger interface area, reduce agglomeration, and improve UV shielding ability.

[0024] Lignin nanosheets, TiH 1.92 / DPPH scavenging rate of lignin flake structure Figure 5 As shown in the figure, the test method for DPPH scavenging rate is as follows: different concentrations of the composite material are added to the DPPH ethanol solution, and then vigorously stirred in the dark to determine its scavenging ability for DPPH. After 5 minutes, the UV-visible absorbance at 517nm is measured every 30 minutes and the average value is taken. The scavenging activity of DPPH can be calculated by the following formula:

[0025]

[0026] Among them, A0 is the absorbance of the blank control, As is the absorbance of the test sample, and A1 is the absorbance of the solution without the composite material. The higher the DPPH removal rate, the better the antioxidant property of the material, which can provide better UV shielding performance. Figure 5 It can be seen that adding TiH 1.92 After that, TiH 1.92 The free radicals react to produce titanium oxide, which improves the DPPH scavenging rate of the composite material.

[0027] TvH 1.92 The SPF value spectrum of / lignin composite materials is as follows Figure 6 As shown, according to the Colipa standard, 100 mg of powder and 900 mg of glycerin were mixed evenly in an agate mortar to prepare a simulated sunscreen with a mass ratio of 1:9. 32.5 mg of the sample to be tested was weighed on a PMMA test plate (5×5 cm) using an analytical balance, and evenly applied with a finger wearing a cot, and the sun protection index of the sample was tested using an SPF meter. The higher the sun protection index, the better the ultraviolet shielding ability, and the value of this embodiment is 8.3.

[0028] Example 2: (1) An appropriate amount of lignin and deionized water were mixed by stirring (mass ratio of 1:10), and the mixture was ball-milled in a ball mill at 300 rpm for 1 h to obtain a lignin nanosheet mixture. The precipitate obtained after centrifugation was freeze-dried to obtain a lignin nanosheet structure.

[0029] (2) Mix an appropriate amount of TiH2 and deionized water by stirring (mass ratio is 1:20), and ball mill the mixture in a ball mill at 300 rpm for 3 hours to obtain a TiH2 nanosheet mixture. Centrifuge and dry. Mix HNO3 and water to prepare an acid wash solution to obtain a 5% nitric acid aqueous solution. Immerse an appropriate amount of titanium hydride powder in the prepared acid wash solution for acid washing (0.25 g / mL) for 90 seconds. The TiH2 nanosheets after acid washing 1.92 The powder was washed thoroughly with deionized water, centrifuged to remove residual acid on the surface, and dried in an oven.

[0030] (3) The powder obtained in step (1) (2) was added to deionized water in a mass ratio of 1:1 and mixed evenly (0.1 g / mL). The obtained suspension was added to an ultrasonic kettle and ultrasonically treated for 10 minutes at a power of 300 W. The suspension was centrifuged at a speed of 5000 rpm for 10 minutes, washed with deionized water, and freeze-dried after centrifugation to obtain TiH 1.92 / lignin two-dimensional nanosheet composites.

[0031] TvH 1.92 The SPF value spectrum of / lignin composite materials is as follows Figure 6 As shown, the value of this embodiment is 8.2.

[0032] Example 3: (1) An appropriate amount of lignin and deionized water were mixed uniformly by stirring (mass ratio was 1:30), and the mixture was ball-milled in a ball mill at 250 rpm for 3 h to obtain a lignin nanosheet mixture. The precipitate obtained after centrifugation was freeze-dried to obtain a lignin nanosheet structure.

[0033] (2) Mix an appropriate amount of TiH2 and deionized water by stirring (mass ratio is 1:10), and ball mill the mixture in a ball mill at 600 rpm for 2 hours to obtain a TiH2 nanosheet mixture. Centrifuge and dry. Mix HNO3 and water to prepare an acid wash solution to obtain a 0.5% nitric acid aqueous solution. Immerse an appropriate amount of titanium hydride powder in the prepared acid wash solution for acid washing (0.05 g / mL) for 180 seconds. The acid washed TiH 1.92 The powder was washed thoroughly with deionized water, centrifuged to remove residual acid on the surface, and dried in an oven.

[0034] (3) The powder obtained in step (1) (2) was added to deionized water at a ratio of 1:6 and mixed evenly (0.35 g / mL). The obtained suspension was added to an ultrasonic kettle and ultrasonically treated at a power of 250 W for 30 minutes. The suspension was centrifuged at 8000 rpm for 8 minutes, washed with deionized water, and freeze-dried after centrifugation to obtain TiH 1.92 / lignin two-dimensional nanosheet composites.

[0035] TvH 1.92 The SPF value spectrum of / lignin composite materials is as follows Figure 6 As shown, the value of this embodiment is 7.9.

[0036] Example 4: (1) An appropriate amount of lignin and deionized water were mixed uniformly by stirring (mass ratio of 1:20), and the mixture was ball-milled in a ball mill at 280 rpm for 2.5 h to obtain a lignin nanosheet mixture. The precipitate obtained after centrifugation was freeze-dried to obtain a lignin nanosheet structure.

[0037] (2) Mix an appropriate amount of TiH2 and deionized water by stirring (mass ratio is 1:20), and ball mill the mixture in a ball mill at 400 rpm for 1 hour to obtain a TiH2 nanosheet mixture. Centrifuge and dry. Mix HNO3 and water to prepare an acid wash solution to obtain a 3.5% nitric acid aqueous solution. Immerse an appropriate amount of titanium hydride powder in the prepared acid wash solution for acid washing (0.12 g / mL) for 120 seconds. The TiH2 nanosheets after acid washing are 1.92 The powder was washed thoroughly with deionized water, centrifuged to remove residual acid on the surface, and dried in an oven.

[0038] (3) The powder obtained in step (1) (2) was added to deionized water in a mass ratio of 5:1 and mixed evenly (0.3 g / mL). The obtained suspension was added to an ultrasonic kettle and ultrasonically treated for 15 minutes at a power of 225 W. The suspension was centrifuged at a speed of 7500 rpm for 8 minutes, washed with deionized water, and freeze-dried after centrifugation to obtain TiH 1.92 / lignin two-dimensional nanosheet composites.

[0039] TvH 1.92 The SPF value spectrum of / lignin composite materials is as follows Figure 6 As shown, the value of this embodiment is 8.1.

[0040] Example 5: (1) An appropriate amount of lignin and deionized water were mixed uniformly by stirring (mass ratio of 1:30), and the mixture was ball-milled in a ball mill at 200 rpm for 2.5 h to obtain a lignin nanosheet mixture. The precipitate obtained after centrifugation was freeze-dried to obtain a lignin nanosheet structure.

[0041] (2) Mix an appropriate amount of TiH2 and deionized water by stirring (mass ratio is 1:10), and ball mill the mixture in a ball mill at 600 rpm for 2 hours to obtain a TiH2 nanosheet mixture. Centrifuge and dry. Mix HNO3 and water to prepare an acid wash solution to obtain a 2.8% nitric acid aqueous solution. Immerse an appropriate amount of titanium hydride powder in the prepared acid wash solution for acid washing (0.2 g / mL) for 90 seconds. The TiH2 nanosheets after acid washing 1.92The powder was washed thoroughly with deionized water, centrifuged to remove residual acid on the surface, and dried in an oven.

[0042] (3) The powder obtained in step (1) (2) was added to deionized water in a ratio of 5:4 and mixed evenly (0.45 g / mL). The obtained suspension was added to an ultrasonic kettle and ultrasonically treated for 25 minutes at a power of 250 W. The suspension was centrifuged at a speed of 9000 rpm for 3 minutes, washed with deionized water, and freeze-dried after centrifugation to obtain TiH 1.92 / lignin two-dimensional nanosheet composites.

[0043] TvH 1.92 The SPF value spectrum of / lignin composite materials is as follows Figure 6 As shown, the value of this embodiment is 8.0. Comparative Example 1: (1) An appropriate amount of lignin and deionized water were mixed uniformly by stirring (mass ratio was 1:20), and the mixture was ball-milled in a ball mill at 200 rpm for 2 h to obtain a lignin nanosheet mixed solution, and the precipitate obtained after centrifugation was freeze-dried to obtain a lignin nanosheet structure.

[0044] (2) An appropriate amount of TiH2 and deionized water were mixed by stirring (mass ratio of 1:10), and the mixture was ball-milled in a ball mill at 400 rpm for 3 h to obtain a TiH2 nanosheet mixture, which was centrifuged and dried.

[0045] (3) The powder obtained in step (1) (2) was added to deionized water in a ratio of 2:1 and mixed evenly (0.15 g / mL). The obtained suspension was added to an ultrasonic reactor and ultrasonically treated for 20 minutes at a power of 250 W. The mixture was centrifuged at a speed of 10,000 rpm for 6 minutes, washed with deionized water, and freeze-dried after centrifugation to obtain a TiH2 / lignin two-dimensional nanosheet composite material.

[0046] Depend on Figure 2 It can be seen that the UV absorption rate of the composite material composed of TiH2 without acid washing is lower than that of other samples, because the excessive hydrogen blocks the UV shielding property of titanium hydride in the composite material. Figure 6 It can be seen that the SPF is 2.9.

[0047] Figure 2 The lignin nanosheets and TiH prepared in Example 1 1.92 、TiH 1.92 / lignin flake structure, TiH prepared in Example 3 1.92 Solid UV absorption spectra of TiH2 flake structure and TiH2 / lignin flake structure samples prepared in Comparative Example 1; Figure 3 The lignin nanosheets and TiH prepared in Example 1 1.92 、TiH 1.92 / lignin flake structure, TiH prepared in Example 3 1.92 Solid UV transmittance spectra of TiH2 flake structure and TiH2 / lignin flake structure samples prepared in comparative example 1.

[0048] Depend on Figure 2 It can be seen that TiH 1.92 Compared with TiH2, it has a lower absorption rate in the non-ultraviolet region, which is consistent with the characteristics of high ultraviolet absorption and low visible light absorption of ultraviolet shielding materials. 1.92 The ultraviolet absorption in the ultraviolet region is higher. From the ultraviolet absorption spectra of Example 1 and Comparative Example 1, it can be seen that Example 1 has a good ultraviolet absorption rate in the ultraviolet region and a low absorption rate in the visible light region. Figure 3 It can be seen that TiH 1.92 Compared with TiH2, it has a lower UV transmittance. From the UV transmittance spectra of Example 1 and Comparative Example 1, it can be seen that the composite material of Example 1 has a lower transmittance in the UV region and a higher transmittance in the visible light region. Figure 2 , Figure 3 It can be seen that TiH 1.92 And composite materials have better UV shielding effect.

[0049] Comparative Example 2: (1) An appropriate amount of lignin and deionized water were mixed uniformly by stirring (mass ratio of 1:10), and the mixture was ball-milled in a ball mill at 300 rpm for 1 h to obtain a lignin nanosheet mixture. The precipitate obtained after centrifugation was freeze-dried to obtain a lignin nanosheet structure.

[0050] (2) Mix an appropriate amount of TiH2 and deionized water by stirring (mass ratio is 1:20), and ball mill the mixture in a ball mill at 300 rpm for 3 hours to obtain a TiH2 nanosheet mixture. Centrifuge and dry. Mix HNO3 and water to prepare an acid wash solution to obtain a 5% nitric acid aqueous solution. Immerse an appropriate amount of titanium hydride powder in the prepared acid wash solution for acid washing (0.25 g / mL) for 90 seconds. The TiH2 nanosheets after acid washing 1.92 The powder was washed thoroughly with deionized water, centrifuged to remove residual acid on the surface, and dried in an oven.

[0051] (3) The powder obtained in step (1) and (2) was added to deionized water at a ratio of 1:10 and mixed evenly (0.55 g / mL). The obtained suspension was added to an ultrasonic kettle and ultrasonically treated at a power of 300 W for 30 minutes. The suspension was centrifuged at a speed of 5000 rpm for 10 minutes, washed with deionized water, and freeze-dried after centrifugation to obtain TiH 1.92 / lignin two-dimensional nanosheet composites.

[0052] The ratio of lignin and titanium hydride in the composite material of this comparative example is not coordinated, and a high content of titanium hydride requires high-power and long-term ultrasonic treatment. However, under this condition, the structure of lignin is destroyed, so the interface bonding of the composite material is not good, and the ultraviolet shielding effect is not good. Figure 6 It can be seen that the SPF is 3.0. Comparative Example 3: (1) An appropriate amount of lignin and deionized water are mixed uniformly by stirring (mass ratio is 1:30), and the mixed solution is ball-milled in a ball mill at 250 rpm for 3 h to obtain a lignin nanosheet mixed solution, and the precipitate obtained after centrifugation is freeze-dried to obtain a lignin nanosheet structure.

[0053] (2) Mix an appropriate amount of TiH2 and deionized water by stirring (mass ratio is 1:10), and ball mill the mixture in a ball mill at 600 rpm for 2 hours to obtain a TiH2 nanosheet mixture. Centrifuge and dry. Mix HNO3 and water to prepare an acid wash solution to obtain a 0.05% nitric acid aqueous solution. Immerse an appropriate amount of titanium hydride powder in the prepared acid wash solution for acid washing (0.05 g / mL) for 180 seconds. After acid washing, the TiH 1.92 The powder was washed thoroughly with deionized water, centrifuged to remove residual acid on the surface, and dried in an oven.

[0054] (3) The powder obtained in step (1) (2) was added to deionized water at a ratio of 1:6 and mixed evenly (0.35 g / mL). The obtained suspension was added to an ultrasonic kettle and ultrasonically treated at a power of 250 W for 30 minutes. The suspension was centrifuged at 8000 rpm for 8 minutes, washed with deionized water, and freeze-dried after centrifugation to obtain TiH 1.92 / lignin two-dimensional nanosheet composites.

[0055] In this comparative example, the titanium hydride was acid-washed with a 0.05% nitric acid aqueous solution, but the acid solution concentration was too low, so that the titanium hydride oxide layer and part of the hydrogen were not washed off, and the ultraviolet shielding effect was poor. Figure 6 It can be seen that the SPF is 3.2.

[0056] Comparative Example 4: (1) An appropriate amount of lignin and deionized water were mixed uniformly by stirring (mass ratio of 1:20), and the mixture was ball-milled in a ball mill at 280 rpm for 2.5 h to obtain a lignin nanosheet mixture. The precipitate obtained after centrifugation was freeze-dried to obtain a lignin nanosheet structure.

[0057] (2) Mix an appropriate amount of TiH2 and deionized water by stirring (mass ratio is 1:20), and ball mill the mixture in a ball mill at 400 rpm for 1 hour to obtain a TiH2 nanosheet mixture. Centrifuge and dry. Mix HNO3 and water to prepare an acid wash solution to obtain a 10% nitric acid aqueous solution. Immerse an appropriate amount of titanium hydride powder in the prepared acid wash solution for acid washing (0.12 g / mL) for 120 seconds. After acid washing, the TiH 1.92 The powder was washed thoroughly with deionized water, centrifuged to remove residual acid on the surface, and dried in an oven.

[0058] (3) The powder obtained in step (1) (2) was added to deionized water in a ratio of 5:1 and mixed evenly (0.3 g / mL). The obtained suspension was added to an ultrasonic kettle and ultrasonically treated for 15 minutes at a power of 225 W. The suspension was centrifuged at 7500 rpm for 8 minutes, washed with deionized water, and freeze-dried after centrifugation to obtain TiH 1.92 / lignin two-dimensional nanosheet composites.

[0059] In this comparative example, the titanium hydride is pickled with a high concentration of nitric acid solution, causing part of the titanium to be corroded and excessively absorb hydrogen, which deteriorates the ultraviolet shielding effect of the composite material. Figure 6 It can be seen that the SPF is 3.0.

[0060] Comparative Example 5: (1) An appropriate amount of lignin and deionized water were mixed uniformly by stirring (mass ratio of 1:30), and the mixture was ball-milled in a ball mill at 200 rpm for 2.5 h to obtain a lignin nanosheet mixture. The precipitate obtained after centrifugation was freeze-dried to obtain a lignin nanosheet structure.

[0061] (2) Mix an appropriate amount of TiH2 and deionized water by stirring (mass ratio is 1:10), and ball mill the mixture in a ball mill at 600 rpm for 2 hours to obtain a TiH2 nanosheet mixture. Centrifuge and dry. Mix HNO3 and water to prepare an acid wash solution to obtain a 2.8% nitric acid aqueous solution. Immerse an appropriate amount of titanium hydride powder in the prepared acid wash solution for acid washing (0.2 g / mL) for 90 seconds. The TiH2 nanosheets after acid washing 1.92 The powder was washed thoroughly with deionized water, centrifuged to remove residual acid on the surface, and dried in an oven.

[0062] (3) The powder obtained in step (1) (2) was added to deionized water at a ratio of 10:1 and mixed evenly (0.55 g / mL). The obtained suspension was added to an ultrasonic kettle and ultrasonically treated at a power of 250 W for 25 minutes. The suspension was centrifuged at a speed of 9000 rpm for 3 minutes, washed with deionized water, and freeze-dried after centrifugation to obtain TiH 1.92 / lignin two-dimensional nanosheet composites.

[0063] In this comparative example, the ratio of lignin to titanium hydride in the composite material is not coordinated. The excess lignin completely covers the titanium hydride nanosheets during the ultrasonic process, which reduces the amount of free radicals absorbed by titanium hydride and converted into titanium oxide, so the ultraviolet shielding effect is poor. Figure 6 It can be seen that the SPF is 3.1.

Claims

1. A method for preparing a TiH2 / lignin two-dimensional nanosheet composite material, characterized in that: The preparation steps are: (1) mixing lignin and deionized water uniformly by stirring, ball-milling the mixture in a ball mill to obtain a lignin nanosheet mixture, and freeze-drying the precipitate obtained after centrifugation to obtain lignin nanosheets; (2) mixing titanium hydride and deionized water uniformly by stirring, ball-milling the mixture in a ball mill to obtain a titanium hydride mixture, centrifuging and drying, immersing the obtained titanium hydride powder in an acid washing solution for acid washing, washing the acid-washed titanium hydride powder with water, centrifuging, and drying to obtain acid-treated titanium hydride; (3) adding the lignin nanosheets obtained in step (1) and the titanium hydride treated with acid in step (2) into deionized water and mixing them evenly; adding the obtained suspension into an ultrasonic kettle, performing ultrasonic treatment, washing after centrifugal separation, and freeze-drying to obtain a titanium hydride / lignin two-dimensional nanosheet composite material.

2. The method for preparing the TiH2 / lignin two-dimensional nanosheet composite material according to claim 1, characterized in that: The step (2) of ball milling is to ball mill the mixed solution in a ball mill at a speed of 300 to 600 rpm for 1 to 3 hours.

3. The method for preparing the TiH2 / lignin two-dimensional nanosheet composite material according to claim 1, characterized in that: The pickling solution in step (2) is a nitric acid aqueous solution with a mass fraction of 0.5% to 5%.

4. The method for preparing the TiH2 / lignin two-dimensional nanosheet composite material according to claim 1, characterized in that: The pickling conditions are as follows: the titanium hydride powder is immersed in a pickling solution at a concentration of 0.05 g / mL to 0.25 g / mL for pickling, and the pickling time is 90 to 180 seconds.

5. The method for preparing the TiH2 / lignin two-dimensional nanosheet composite material according to claim 1, characterized in that: The mass ratio of the lignin nanosheets in step (1) to the titanium hydride after acid treatment in step (2) is 1:(0.2-6).

6. The method for preparing the TiH2 / lignin two-dimensional nanosheet composite material according to claim 1, characterized in that: The power of the ultrasonic treatment in step (3) is 200 to 300 W, and the ultrasonic treatment time is 10 to 30 minutes.

7. A TiH2 / lignin two-dimensional nanosheet composite material prepared according to the method according to any one of claims 1 to 6.

8. Use of the TiH2 / lignin two-dimensional nanosheet composite material prepared according to the method according to any one of claims 1 to 6 in ultraviolet shielding products.

Citation Information

Patent Citations

  • Aging-resistant, transparent and heat-insulating nanometer glass paint and preparation method thereof

    CN105838217A

  • Lignin-modified titanium dioxide particles and preparation method and application thereof

    CN108938450A

  • Self-expanding lignofoam compositions and lignofoams made therefrom

    CN111825995A

Cited By

  • Lignin intercalation two-dimensional nano material as well as preparation method and application thereof

    CN120771840A